Open-end mutual funds and capital-gains taxes - Barclay, Michael J.; Pearson, Neil D.; Weisbach, Michael S. (Journal of Financial Economics, 1998)
Despite the fact that taxable investors would prefer to defer the realization of capital gains indefinitely, most open-end mutual funds regularly realize and distribute a large portion of their gains. We present a model in which unrealized gains in the fund's portfolio increase expected future taxable distributions, and thus increase the present value of a new investor's tax liability. In equilibrium, managers interested in attracting new investors pass through taxable capital gains to reduce the overhang of unrealized gains. This model contains a number of empirical predictions that are consistent with data on actual fund overhangs.